Decision modelsin the management of tree cover atcattle farms of Nariño - Muñoz G., Diego Andrés; Navia E., Jorge Fernando; Moreno, Beto (Revista de Ciencias Agrícolas, 2014)
Decision-making by farmers of the activities conducted at their farms has a direct or indirect influence on tree cover, affecting its structure, density, and composition. This study was conducted at the municipalities of Guachucal and Cumbal, in the department of Nariño, Colombia, with the aim of identifying the criteria and key decisions made by farmers in the management of tree cover in milk-producing cattle farms. The decisions were modeled and simulated in the program Netica 2.6. General decision models were designed from the obtained responses, which yielded four major and most influential events in the management of tree cover: 1) pruning event, 2) weed control event, 3) tree planting event, and 4) tree use event. The frequencies allowed us to estimate the probability of each decision and the influence of variables regarding the events for its subsequent modeling and simulation. In addition, in order to further study the process of decision-making, scenarios relating to agro-ecological conditions of the farm, management of the productive unit, and the environment in which the farm operates were proposed. Furthermore, the main constraints to the management and establishment of tree cover were analyzed. The most important event in the management of tree cover is pruning, given its value in obtaining firewood for fuel, and this factor influences the increase of tree cover as living fences in the zone.